Potential Empowering MSME Entrepreneurs in Dupa to Support Production and Marketing Enhancement in Sangeh Village, Abiansemal District - PURNAMAWATI, Ida Ayu Putu Santi; PUTRA, I Komang; DEWI, I Gusti Ayu Agung Istri Sari (PT Batara Swastika Harati, 2024)
This Community Partnership Program (PKM) aims to empower Dupa Ayu Bagus Angkar MSMEs located in Sangeh Village, Abiansemal District, Badung Regency, Bali, in addressing various business challenges. The program identifies key issues the MSMEs face, including inadequate production facilities, suboptimal digital marketing, and manual financial management. Through a solution-based approach, the program includes training in digital marketing and financial management using Microsoft Excel and providing production tools such as digital scales and fragrance dispensers. The program's outcomes show improvements in production capacity, optimization of digital marketing strategies, and enhanced financial management for Dupa Ayu Bagus Angkar MSMEs. As a result, the program is expected to increase the competitiveness and sustainability of MSMEs in an increasingly competitive market and positively impact the local economy in Bali.